Water Supply and Water Management in the Metal Ages (Archaeopress Publishing, 2025)
Water Supply and Water Management in the Metal Ages gathers papers originally presented at the Metal Ages 2022 colloquium, hosted by the Archaeology Department of Bilkent University, Ankara and bringing together the UISPP’s Scientific Commissions ‘Metal Ages in Europe and the Mediterranean’ and ‘Archaeometry of Prehistoric and Protohistoric Inorganic Artefacts, Materials and their Technologies’ for their respective annual meetings.Five of the papers included here focus specifically on water supply and water management. Others cover copper metallurgy, pottery studies and fighting techniques, and overall they range chronologically from the Chalcolithic to the Late Iron Age, and geographically from Iran to Iberia. A significant number of papers cover topics focusing on artefact archaeometry, due to the participation in the Ankara colloquium of many colleagues from the UISPP’s Archaeometry commission.The publication of these proceedings in their present format was made possible thanks to generous financial support by Valentín de Torres Solanot and E2IN2.